Peningkatan Keterampilan Berbahasa melalui Teknik Reportase Mahasiswa Program Studi Komunikasi dan Penyiaran Islam (KPI) IAIN Syaikh Abdurrahman Siddik Bangka Belitung - Eva Harista (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
This study aims to improve language skills (listening, reading, speaking, and writing) KPI Study Program students Semester VI 2017/2018 Academic Year, Da'wah and Communication Department, IAIN Syaikh Abdurrahman Siddik Bangka Belitung through reportage techniques. This type of research is classroom action research (CAR). The design in PTK consists of three cycles in which there are four components in each cycle, namely planning, implementing actions, results of actions, and reflection. In this CAR, researchers used the Elliot model with modifications. This research is the result of learning from the Indonesian Language Discourse course for KPI. The subjects in this study were the sixth semester students of the Islamic Communication and Broadcasting Study Program (KPI) totaling 9 students. The results showed that in the first cycle, the average grade was 74.66 with a fairly good category. In cycle II students' language skills experienced a slight increase. This can be seen from the average grade, which is increased to 79.66 with a good enough category. The increase in the average grade from cycle I to cycle II is 5.00. In cycle III there was a significant increase with 85.77 class average value. Language skills in cycle III can be categorized as good. As for increasing the average grade from cycle II to cycle III, which is 6.11.